P107 Targeting activated synovial fibroblasts using photodynamic therapy in experimental arthritis. (21st February 2018) - Dorst, DN; Rijpkema, M; Buitinga, M; Brom, M; Bos, DL; Freimoser, A; Klein, C; Walgreen, B; van der Kraan, PM; Gotthardt, M; Koenders, MI
Abstract : Introduction: Activated synovial fibroblasts (SF) are characterised by the expression of Fibroblast Activation Protein (FAP). Here, we investigated the potential of photodynamic therapy (PDT) targeting FAP to selectively induce cell death in these cells. In PDT, a light-sensitive molecule is delivered to a target cell and activated with light of a specific wavelength. This causes cell death through the production of reactive oxygen species. Methods: The anti-FAP antibody 28 H1 was conjugated with the photosensitizer IRDye700DX (28H1-700DX). In vitro PDT assays were performed with 3 T3 fibroblasts stably transfected with FAP. 3T3-FAP cells were incubated with 28H1-700DX or a control conjugate for 4 hours, and exposed to varying 690 nm light doses. Subsequently, cell viability was measured using the CellTiter-Glo assay. For in vivo biodistribution, 5 days after onset of antigen-induced arthritis (AIA) C57Bl6 mice were injected with 28H1±700 DX labelled with radioactive Indium for quantification purposes (expressed as% injected dose per gram tissue (%ID/g)). For the PDT treatment experiment, arthritic mice were injected at day 5 of AIA with 28H1-700DX or PBS and exposed to 50 or 90 J/cm 2 light 24 hours post injection. Joints were isolated at day 10 for histological analysis. Results: To assess PDT efficacy, we applied 13.7 J/cm2 light exposure to 3T3-FAP cells incubated with 6.67 pM 28H1-700DX, which significantly reduced cell viability (89.27%±2.48 compared to control (p<0.001)). No cell death was observed with the control 700DX-conjugate. Conjugating the anti-FAP antibody to 700DX changed the in vivo biodistribution of the antibody, with a higher accumulation in the liver (27, 06±0, 95%ID/g vs. 6, 08±0, 42%ID/g with control (p<0, 001)) and lower blood levels (5, 32±0, 36%ID/g vs. 12, 72±0, 80%ID/g with control (p<0, 001)). Accumulation in the arthritic joints was not significantly different. Histological analysis of the PDT-treated mouse knee joints is ongoing. Conclusions: We have demonstrated fibroblast-specific cell death using 700DX-conjugated 28 H1 PDT, indicating FAP-based PDT as a promising new tool in treating RA. Furthermore, we demonstrated that adding 700DX results in faster liver clearance of the antibody, but does not affect uptake in the inflamed knee joint. Future research will further elucidate the applicability of our conjugate for PDT in animal models of RA. Disclosure of interest: None declared